Semantic Web Technology: Towards Meaningful Retrieval - Dutta, Biswanath (Journal of Information and Knowledge, 2006)
The World Wide Web has a great impact on the way people communicate and their transactions. It has helped transform communities towards knowledge economy, broadly speaking into a knowledge society. Now the web is facing a significant change since its inception, and Sir Tim Berners-Lee is again at the forefront of the change introducing the concept of Semantic Web. In this paper, an overview of Semantic Web technology and its prospects are presented. It explains the different layers involved in the implementation of semantic web for representing information on the web. The paper discusses applications of semantic web technology in information retrieval.